THE EFFECT OF COCOPEAT AND HYDROTON GROWING MEDIA ON TOMATO PLANT GROWTH - Julkarnain Julkarnain; Muanah Muanah; Suhairin Suhairin; Marianah Marianah; Ida Wahyuni; Earlyna Shintia Dewi (Protech Biosystems Journal, 2025)
This study aims to determine the effect of cocopeat and hydroton growing media on the growth of tomato plants (Lycopersicum esculentum Mill.) in polybag cultivation systems. The research used an experimental method with a Completely Randomized Design (CRD), comprising six treatments and four replications. Observed parameters included plant height, leaf number, root length, and fresh and dry plant weights. The results showed that treatment P5 (50% soil + 50% hydroton) yielded the best outcomes across most parameters, such as plant height (47.75 cm), leaf number (12.50), root length (24.75 cm), and fresh stem weight (24.75 g). Conversely, treatment P2 (100% cocopeat) showed the lowest growth results. The study concludes that a combination of soil and hydroton is the most effective growing medium for supporting tomato plant growth. Further research is recommended through the generative phase to evaluate yield effects.